Prediction of Flexural Strength of Soilcrete Blocks Using Scheffe’s Simplex Lattice Design - C.E. Okere; N.N. Osadebe; D.O. Onwuka (International Journal of Computer Sciences and Engineering, 2014)
The major constituent material in block production which is river sand, is costly, scarce and unavailable in some places. This has serious effect on the production cost of blocks used in construction. Flexural strength which is an important mechanical property has been ignored to an extent with regards to block moulding technology. This work presents the flexural strength of soilcrete blocks made with readily available and affordable late rite and the optimization of the flexural strength using Scheffeï¿½s simplex lattice design method. Statistical tools were used to verify the proposed optimization technique. The optimum value of the flexural strength is 1.452N/mm2.